Object of relations on use and protection of water resources in the new Water code of the Republic of Belarus - Sereda, Elena L. (Journal of the Belarusian State University. Law, 2019)
The article is devoted to changes in water legislation, taking into account the adoption of the new Water Code of the Republic of Belarus of 30 April 2014. The author analyzes the concept of «water» and «water objects» and «groundwater» of their use and protection. Groundwater represents the major part of the waters of the Republic of Belarus. Rational use of water resources and their protection are the key to achieving sustainable development of the state. So, the author makes suggestions for improving the current legislation, namely the consolidation of such legal categories, such as «water», «groundwater» and «the state water fund».
Keywords: The Water Code of the Republic of Belarus; water; water protection; right to water use; groundwater; state water fund; water use; water resources